Cognition and intelligence: identifying the mechanisms of the mind - Sternberg, Robert J.; Pretz, Jean E. (Cambridge University Press, 2005)
"In 1957, Lee Cronbach called on the membership of the American Psychological Association to bring together experimental and differential approaches to the study of cognition. The field of intelligence research is an example of a response to that call, and Cognition and Intelligence: Identifying the Mechanisms of the Mind investigates the progress of this research program in the literature of the Mind investigates the progress of this research program in the literature of the past several decades. With contributions from formative experts in the field, including Earl Hunt and Robert Sternberg, this volume reviews the research on the study of intelligence from diverse cognitive approaches, from the most bottom-up to the most top-down. The authors present their findings on the underlying cognitive aspects of intelligence based on their studies of neuroscience, reaction time, artificial intelligence, problem solving, metacognition, and development. The book summarizes and synthesizes the literature reviewed and makes recommendations for the pursuit of future research in the field."--Jacket